Diminishing Partnership as Solution to Turkey's Housing Crisis: An Analysis from Islamic Law Perspective - Kahraman, Abdullah; Uddin, A H M Ershad (International Journal of Economics, Management and Accounting, 2026)
The concept of decreasing musharakah or al-Musharakahtu'l-mutanaqisah involves a capital operation within a partnership, culminating in the transfer of ownership. Unlike traditional practices, this partnership model emerged in the 20th century and has since become a specialized arrangement in contemporary financial practices, notably within interest-free financial institutions or participation banks. In diminishing musharakah, the financial institution gradually reduces its share in the partnership until it is wholly transferred to the customer, who then assumes the role of managing partner. This arrangement aims at providing interest-free financing while generating profits for all involved parties, offering diverse banking services beyond permanent musharakah setups. It entails multiple individuals joining forces in an income-generating venture, with one party progressively acquiring the shares of others until they gain sole ownership through successive independent sales contracts. Diminishing musharakah is an alternative to conventional methods, particularly within interest-free financial institutions across industry, trade, agriculture, and tourism. This research investigates integrating diminishing partnership systems into Turkish housing finance, primarily through Ijarah-based diminishing musharakah financing methods, post the pandemic-induced housing crisis. The study identifies infrastructure, staff training, and product competitiveness as areas needing improvement in the participation banking sector, suggesting legal adjustments and regulatory frameworks for effective implementation. This research emphasizes the necessity of comprehensive legislative changes within Turkey's financial framework to accommodate diminishing partnership systems. It offers original insights and proposes legal amendments that uniquely contribute to participatory banking research. It presents a fresh perspective on home financing, promoting economic autonomy and housing market accessibility through innovative approaches.